An Evaluation of Ontario Provincial Land Use and Resource Management Policies and Their Intersection with First Nations with Respect to Manifest and Latent Content - Summary Table - McLeod, Fraser; Viswanathan, Leela; Whitelaw, Graham; Macbeth, Jared; McCarthy, Daniel; Alexiuk, Erin (2016)
For further information into the expanded analysis developed from the initial table and the broader findings of the research, please refer to: McLeod, F., Viswanathan, L., Whitelaw, G., Macbeth, J., King, C., McCarthy, D., Alexiuk, E. (2015). “Finding Common Ground: A Critical Review of Land Use and Resource Management Policies in Ontario, Canada and their Intersection with First Nations.” International Indigenous Policy Journal, 6 (1). For more information about the Planning with Indigenous Peoples (PWIP) Research Group, visit www.queensu.ca/pwip. This summary table entitled An Evaluation of Ontario Provincial Land Use and Resource Management Policies and Their Intersection with First Nations with Respect to Manifest and Latent Content represents a condensed version of the initial analysis executed in summer 2013 and revisited in spring 2014 to evaluate the manifest and latent content of 337 provincial texts. This research, supported by various grants from the Social Sciences and Humanities Research Council of Canada (SSHRC) was completed as part of the requirements for a 2014 School of Urban and Regional Planning at Queen’s University M.Pl thesis by Fraser McLeod entitled Finding Common Ground: Building Equitable Planning Futures with First Nations in Ontario, Canada. As part of this thesis research, additional analysis not included in this table was carried out, including subsequent rounds of targeted analysis, semi-structured interviews for validation purposes only and ongoing iterative discussions and active involvement by team members of the Planning With Indigenous Peoples (PWIP) Research Group at Queen’s University (See www.queensu.ca/pwip). This table is a reduced version of the initial database that was expanded and used to execute further analysis. It should be acknowledged that this table presented in this reduced and simplified form has limitations and does not capture the depth of the analysis, to a certain degree. For instance, not all provincial texts examined as part of the analysis are ...